(untitled) (Research, Society and Development, 2021)
Introduction: Acromegaly is a syndrome manifested by hypersecretion of GH and IGF-1, which has consequences on cartilage closure, metabolic changes such as glucose intolerance and cardiovascular changes such as arterial hypertension. In most cases, this syndrome is linked to somatotropinomas in the Master Gland and is difficult to diagnose, as it has an insidious onset, usually noticed after 5 years of its onset. This condition affects the quality and average length of life of those who have it. Laboratory diagnosis can be done by measuring basal GH and IGF-1. As for the conduct, the first choice therapy is surgical, however, like any procedure, it presents complications. Thus, the objective is a better treatment and differentiated conduct, through the clarification of this situation regarding the postoperative period. Methodology: A literature review was carried out in the VHL, using the descriptors: “Acromegaly” AND “Postoperative Complications” from 2011 to 2021, with 16 selected articles. Results and discussion: Among the findings, it is observed that the endoscopic transsphenoidal approach is more advantageous in relation to the others. In addition, postoperative complications were classified into four categories: Complications related to the surgical procedure, such as infections and hemorrhages; ischemic complications; hormonal complications such as diabetes insipidus and GH tumor-related complications such as obstructive sleep apnea. Conclusion: Better management of patients with acromegaly after surgery is necessary, as this has the particularity related to sleep disorders, so that the conduct can be individualized and improved.